Evaluation of Women's Empowerment in a Community-Based Human Papillomavirus Self-Sampling Social Entrepreneurship Program (Hope Project) in Peru: A Mixed-Method Study - Shin, Michelle B.; Garcia, Patricia J.; Dotson, Mary Elizabeth; Valderrama, María; Chiappe, Marina; Ramanujam, Nimmi; Krieger, Marlee; Ásbjörnsdóttir, Kristjana; Barnabas, Ruanne V.; Iribarren, Sarah J.; Gimbel, Sarah (Frontiers in Public Health, 2022)
Introduction: Understanding community women’s relational and financial empowerment in social entrepreneurship could be the key to scaling up community-based human papillomavirus (HPV) self-sampling programs in low- and middle-income countries. The Hope Project, social entrepreneurship in Peru, trains women (Hope Ladies) to promote HPV self-sampling among other women in their communities. This study aims to evaluate the Hope Ladies’ relational and financial empowerment after participating in the program. Materials and Methods: We evaluated the Hope Ladies’ experiences of empowerment in social entrepreneurship using a parallel convergent mixed methods design. The Hope Ladies participated in semi-structured in-depth interviews (n= 20) and an eight-questions five-point Likert scale survey that evaluated their relational (n=19)/financial (n=17) empowerment. The interview and the survey questions were developed using three empowerment frameworks: Kabeer’s conceptual framework, International Center for Research on Women’s economic empowerment indicators, and the Relational Leadership Theory. Deductive content analysis was used to evaluate the interviews with pre-determined codes and categories of empowerment. Descriptive statistics were used to analyze the survey results. Qualitative and quantitative data were integrated through a cross-case comparison of emergent themes and corresponding survey responses during the results interpretation. Results: All Hope Ladies reported experiencing increased empowerment in social entrepreneurship. Interviews: The women reported challenges and improvement in three categories of empowerment: 1) resources (balancing between household and Hope Lady roles, recognition from the community as a resource, camaraderie with other Hope Ladies); 2) agency (increased knowledge about reproductive health, improved confidence to express themselves, and ability to speak out against male-dominant culture); and 3) achievement (increased economic assets, improved ability to make financial decisions, and widened social network and capital, and technology skills development). Survey: All (100%) agreed/totally agreed an increase in social contacts, increased unaccompanied visits to a healthcare provider (86%), improved confidence in discussing reproductive topics (100%), improved ability to make household decisions about money (57% pre-intervention vs. 92% post-intervention). Conclusions: The Hope Ladies reported improved relational and financial empowerment through participating in community-based social entrepreneurship. Future studies are needed to elucidate the relationship between empowerment and worker retention/performance to inform the scale-up of HPV self-sampling social entrepreneurship programs.